Temperature sensitivity of mineral soil carbon decomposition in shrub and graminoid tundra, west Greenland. Issue 1 (December 2016) - Bradley-Cook, Julia; Petrenko, Chelsea; Friedland, Andrew; Virginia, Ross
Abstract Background Shrub expansion is transforming Arctic tundra landscapes, but the impact on the large pool of carbon stored in high-latitude soils is poorly understood. Soil carbon decomposition is a potentially important source of greenhouse gases, which could create a positive feedback to atmospheric temperature. Decomposition is temperature sensitive, but the response to temperature can be altered by environmental variables. We focus on mineral soils, which can comprise a substantial part of the near-surface carbon stock at the landscape scale and have physiochemical characteristics that influence temperature sensitivity. We conducted a soil incubation experiment to measure carbon dioxide (CO2 ) emissions from tundra soils collected from west Greenland at two depths of mineral soils (0-20 cm and 20-40 cm below the surface organic horizon) incubated at five temperatures (4, 8, 12, 16, 24 °C) and two moisture levels (40 % and 60 % water holding capacity). We used an information theoretic model comparison approach to evaluate temperature, moisture and depth effects, and associated interactions, on carbon losses through respiration and to determine the temperature sensitivity of decomposition in shrub- and graminoid-dominated soils. Results We measured ecologically important differences in heterotrophic respiration and temperature sensitivity of decomposition between vegetation types. Graminoid soils had 1.8 times higher cumulative respiration and higher temperature sensitivity (expressed as Q-10) in the shallow depths (Q-10graminoid = 2.3, Q-10shrub = 1.8) compared to shrub soils. Higher Q-10 in graminoid soils was also observed for the initial incubation measurements (Q-10graminoid = 2.4, Q-10shrub = 1.9). Cumulative respiration was also higher for shallow soils, increased with moisture level, and had a temperature-depth interaction. Increasing soil moisture had a positive effect on temperature sensitivity in graminoid soils, but not in shrub soils. Conclusion Mineral soil associated with graminoid-dominated vegetation had greater carbon losses from decomposition and a higher temperature sensitivity than shrub-dominated soils. An extrapolation of our incubation study suggests that organic carbon decomposition in western Greenland soils will likely increase with warming and with an increase in soil moisture content. Our results indicate that landscape level changes in vegetation and soil heterogeneity are important for understanding climate feedbacks between tundra and the atmosphere.